PENGELOLAAN PROGRAM SEKOLAH EFEKTIF DI SEKOLAH DASAR NEGERI BULUKANTIL KECAMATAN JEBRES - Budiarto, Rosid (2011)
The objectives of the research are to analyze and describe: 1) the characteristics of effective school programs management in public elementary school of Bulukantil of Jebres Sub District of Surakarta; and 2) the characteristics of supporting and inhibiting factors in effective school program management in Public Elementary School of Bulukantil of Jebres Sub District of Surakarta. The type of the research based on its approach is a qualitative research with a case study. The research was undertaken in Public Elementary School of Bulukantil of Jebres Sub District of Surakarta. The object of the research was school program management in public elementary school of Bulukantil of Jebres Sub District of Surakarta. The subjects of the research is the principal of public elementary school of Bulukantil of Jebres Sub District of Surakarta. The data collecting method is done using observation, in-depth interview, and document techniques. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The data validation is done using data triangulation, member check, and key informant review techniques. Based on the analysis, the research concludes that: 1) the characteristics of effective school program management in public elemen tary school of Bulukantil of Jebres Sub District of Surakarta convey the aspects of planning, acting, and controlling. SWOT analysis is done prior to the the program planning. Based on such analysis, the school implements various strategies in school devel opment program. All the decision is taken based on participatory decision making; 2) The supporting factors in effective school program management in public elementary school of Bulukantil of Jebres Sub District of Surakarta convey the physical facilities, human resources, parental support and school board. The inhibiting factor in effective school program management in public elementary school of Bulukantil of Jebres Sub District of Surakarta convey the financing matters.